Simbolismul solstițiului de vară. Lecturi comparative, Iosefina Blazsani-Batto: Symbolism of the summer solstice: comparative readings, Iosefina Blazsani-Batto - Dimitriu, Carmen (Swedish Journal of Romanian Studies, 2023)
In the book Symbolism of the Summer Solstice: Comparative Readings, Iosefina Blazsani-Batto approaches, through a comparative perspective, a theme with wide resonances in Romanian folkloric mythology, but also in the universal one, taken up by many historians of religions, exegetes and, last but not least, writers. The wide area of research reflects the author's desire to document as well as possible the scholarly approach to the theme and to give secondary importance to field sources, as well as to imaginative elaborations of them. The research, especially through its various hermeneutic possibilities, is a meritorious achievement which, complemented by the author's constant preoccupation with this field, offers a textually illustrated field of analysis of the subject, both in terms of theory (ethnography) and folklore and literature.